2017
DOI: 10.1002/chem.201700494
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Supported E3 Clusters (E=Si–Sn)

Abstract: The interaction among E (E=Si, Ge, Sn) clusters and different ligands (L) encompassing five carbon-based donors (cyclic (alkyl)(amino)carbene (cAAC), N-heterocyclic carbene (NHC), saturated NHC (SNHC), mesoionic carbenes (MIC1, and MIC2)), two nitrogen-based donors (trimethylamine and pyridine), and two phosphorous-based donors (phosphinine and trimethylphosphine) in E (L) complexes is explored through DFT computations. Although all carbenes form very strong bonds with E clusters, cAAC makes the strongest bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 164 publications
1
12
0
Order By: Relevance
“…As noted in previous reports, in Si 3 (cAAC) 3 , one ligand is bent upward and the another two are bent downward with respect to the plane of the Si 3 cluster. , In the naked Si 3 cluster, one Si–Si distance is longer by 0.532 Å than the other two equal Si–Si distances in the most stable C 2 v geometry, whereas upon complexation with cAAC, the difference between the longest and the shortest Si–Si bond is reduced to only 0.042 Å. This was also observed previously .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…As noted in previous reports, in Si 3 (cAAC) 3 , one ligand is bent upward and the another two are bent downward with respect to the plane of the Si 3 cluster. , In the naked Si 3 cluster, one Si–Si distance is longer by 0.532 Å than the other two equal Si–Si distances in the most stable C 2 v geometry, whereas upon complexation with cAAC, the difference between the longest and the shortest Si–Si bond is reduced to only 0.042 Å. This was also observed previously .…”
Section: Resultssupporting
confidence: 86%
“…24 After that, some of us performed a benchmarking study on nine different types of carbenes to explore their relative strength in complexation with Si 3 and expanded this idea to the heavier analogues of the Si 3 cluster. 25 A ligand stabilized C 3 molecule or other species in these series are hitherto unknown. In 2006, the group of Bertrand became successful in isolation of a cyclopropenylidene derivative that is stable at room temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, Δ E disp represents the dispersion interaction between the two fragments. This method is very widely used to analyze the bonding situation in different type of systems [61,62,63,64,65,66,67,68,69,70,71].…”
Section: Ng Compounds Under the Light Of Theoretical Chemistrymentioning
confidence: 99%
“…Such divalent C(0) complexes are termed as carbones . The class of suitable ligands for carbones CL 2 has been extended with the synthesis of N-heterocyclic carbene (NHC) and cyclic (alkyl)­(amino) carbene (cAAC) ligands and they have been widely used to prepare exciting complexes. The intriguing bonding situation of C­(PPh 3 ) 2 stimulated the search for other carbone complexes, which led to the prediction of carbodicarbene, C­(NHC) 2 in 2007 . In the following year, two different groups experimentally synthesized a benzoannulated derivative C­(NHC Bz ) using different synthetic routes. , It has been gradually extended to a wide varieties of ligands containing a L→C(0)←L bonding motif. Besides L→C(0)←L σ donation there is also some L←C(0)→L π backdonation, the extent of which depends on the π accepting ability of L. Bonding analysis also showed that the bonding between carbon and cAAC ligands in C­(cAAC) 2 is best represented as electron-sharing interaction (cAAC)C(cAAC) .…”
Section: Introductionmentioning
confidence: 99%